Peer support for CKD patients and carers: overcoming barriers and facilitating access. (3rd February 2015) - Taylor, Francesca; Gutteridge, Robin; Willis, Carol
Abstract: Background: Peer support is valued by its users. Nevertheless, there is initial low take‐up of formal peer support programmes among patients with chronic kidney disease (CKD), with fewer patients participating than expressing an interest. There is little evidence on reasons for low participation levels. Few studies have examined the perspectives of carers. Objective: To explore with CKD patients and carers their needs, wants and expectations from formal peer support and examine how barriers to participation may be overcome. Methods: Qualitative interviews with a sample of 26 CKD stage five patients and carers. Principles of Grounded Theory were applied to data coding and analysis. Setting: Six NHS Hospital Trusts. Results: Whilst informal peer support might occur naturally and is welcomed, a range of emotional and practical barriers inhibit take‐up of more formalized support. Receptivity varies across time and the disease trajectory and is associated with emotional readiness; patients and carers needing to overcome complex psychological hurdles such as acknowledging support needs. Practical barriers include limited understanding of peer support. An attractive peer relationship is felt to involve reciprocity based on sharing experiences and both giving and receiving support. Establishing rapport is linked with development of reciprocity. Conclusions: There is potential to facilitate active uptake of formal peer support by addressing the identified barriers. Our study suggests several facilitation methods, brought together in a conceptual model, including clinician promotion of peer support as an intervention suitable for anyone with CKD and their carers, and opportunity for choice of peer supporter.